The Cost of Lung Cancer in Alberta - Sandor J Demeter; Philip Jacobs; Chester Chmielowiec; Wayne Logus; David Hailey; Konrad Fassbender; Alexander McEwan (Canadian Respiratory Journal)
BACKGROUND: Lung cancer is the leading cause of cancer morbidity and mortality. In addition, lung cancer has a significant economic impact on society.